Editorial: Mycorrhizal fungi and plants in terrestrial ecosystems, volume II - Hijri, Mohamed; Bâ, Amadou (Frontiers in Plant Science, 2023)
In 1885, Frank reported a mutualistic symbiotic relationship between a fungus and its host in which both organisms nutritionally relied on each other (Frank & Trappe, 2005). He observed that mycorrhizal associations were widespread across a variety of habitats and soils, contrary to the general thinking of the nineteen centuries. This suggested that mycorrhizae play a substantial role in ecosystem diversity, functioning and stability. Arbuscular mycorrhizal (AM) associations are the most widespread among all types of mycorrhiza, estimated to involve more than 80% of all plant species. These associations are characterized by the formation of intercellular and intracellular hyphae, as well as specialised branching hyphae create two distinct structures: coils in Arum-type and arbuscules in Paris-type arbuscular mycorrhizae, in the root epidermis and cortical cells. In some species, vesicles or swollen hyphal structures may also develop, both intra- and extraradical hyhae. AM fungal spores of certain genera are found on both intraradical and extraradical hyphae, and auxiliary cells are sometimes produced in the extraradical mycelium of some species. All of these fungi belong to the phylum Glomeromycota. AM symbiosis is found in a variety of plants, from liverworts and ferns to conifers and angiosperms. However, there are some angiosperms that do not form AM symbiosis. Among these non-host species members of Brassicaceae are believed to be a non-host for arbuscular mycorrhizal fungi (AMF).